The Integrative Nature of Interculturalism in Galicia at The Beginning of the 20th Century - Sokol, Mariana (2021)
The article outlines the main aspects of interculturalism in Galicia at the beginning of the 20th century. The interculturalism has been defined as the initial basis of communication, formed by a combination of social and educational environment. In modern society with many political and intercultural problems, the communicative competence and formation of tolerant attitudes towards people play a significant role. Linguistic education is one of the main tasks of educational pedagogy, linguistics, methodology, language rules, principles, and methods of teaching, ways of investigating education. The level of language culture of the personality in the mother tongue and foreign languages is evidence of the development of linguistic competence. The changes in the cultural sphere of society determine the need to investigate linguistic problems, focusing on improving language culture to achieve efficiency. The language problems have gone beyond the framework of philology and have become the general problems of society to regulate language culture in the process of social communication, social processes, the development of society as a whole system. In the political sphere, the culture of language promotes the emergence of mutual interest and respect between people of different nationalities and the stabilization of interethnic and international relations. The described innovative approach in the organization of social communication and interculturalism in Galicia space can be creatively and practically adapted in the conditions of any modern multicultural society.